1984
DOI: 10.1084/jem.159.4.1117
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against human T cell leukemia-lymphoma virus (HTLV) p24 internal core protein. Use as diagnostic probes and cellular localization of HTLV.

Abstract: Four monoclonal antibodies, human T cell leukemia-lymphoma virus (HTLV) 6, 7, 8, and 9, which react with the 24,000 dalton internal core protein of HTLVI, have been developed. These monoclonal antibodies reacted with only HTLV-infected cells and not with a broad spectrum of normal, neoplastic, mitogen-stimulated, or virus-infected cells and tissues. HTLV 6, 7, 8, and 9 identified at least two different antigenic determinants on HTLV p24 that were also recognized by antibodies present in HTLV+ patient sera. Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 26 publications
(40 reference statements)
0
15
0
1
Order By: Relevance
“…Female BALB/c mice were similarly immunized with recombinant LF (rLF; List Biological Laboratories, Campbell, CA), and spleens were harvested and used to make hybridomas. Immune spleen cells were fused with mouse myeloma cells using standard procedures routinely used in our laboratory (14,31,35,44,45,52,55). Hybridomas producing anti-rPA or anti-rLF antibodies were screened by enzyme-linked immunosorbent assay (ELISA) using rPA or rLF as the coating antigen, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Female BALB/c mice were similarly immunized with recombinant LF (rLF; List Biological Laboratories, Campbell, CA), and spleens were harvested and used to make hybridomas. Immune spleen cells were fused with mouse myeloma cells using standard procedures routinely used in our laboratory (14,31,35,44,45,52,55). Hybridomas producing anti-rPA or anti-rLF antibodies were screened by enzyme-linked immunosorbent assay (ELISA) using rPA or rLF as the coating antigen, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-HTLV p19 was shown to react not only with HTLV-infected lymphocytes but also with the thymus tissue of seronegative humans and syncytial trophoblast cells from normal human placenta (RobertGuroff et al, 1981). Monoclonal antibodies against p24 (Palker et al, 1984;Fujii et al, 1984) and gp21 (Sugamura et al, 1984a) have also been reported. Anti-p24 antibody has been used to identify a precursor protein, p53 (Fujii et al,t984).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…13,14 Definitions In this study, a seropositive serum sample was defined by the presence of antibodies to gag (p24) and env (gp46 or precursor gp61/68) on WIB or RIPA. 'o A serum sample with immunoreactivity to at least one HTLV-I gene product but not satisfying these criteria was called indeterminate.…”
Section: Serum Specimensmentioning
confidence: 99%